2021
DOI: 10.1364/oe.412224
|View full text |Cite
|
Sign up to set email alerts
|

High power tunable multiwavelength random fiber laser at 1.3 μm waveband

Abstract: Multiwavelength fiber lasers, especially those operating at optical communication wavebands such as 1.3 μm and 1.5 μm wavebands, have huge demands in wavelength division multiplexing communications. In the past decade, multiwavelength fiber lasers operating at 1.5 μm waveband have been widely reported. Nevertheless, 1.3 μm waveband multiwavelength fiber laser is rarely studied due to the lack of proper gain mechanism. Random fiber laser (RFL), owing to its good temporal stability and flexible wavelength tunabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Another way to generate widely tunable RFLs is through the combination of tunable pump lasers and cascaded Raman lasing [23][24][25][26][27]. In addition, nearly octave wavelength-tunable RFLs covering a 1-1.9 µm region have been realized by pump wavelength tuning and cascaded Raman shifting, whereas the S-, C-and L-band lasing requires a sixth-to eighthorder cascaded Raman process which requires a high threshold and for which it is difficult to control the lasing bandwidth due to the use of a broadband reflector [23][24][25][26][27][28][29]. On the other hand, the glass hosts (tellurite and bismuth oxide-based glasses) with high refractive indexes have been considered for expanding the gain bandwidth and the tunable range of fiber lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to generate widely tunable RFLs is through the combination of tunable pump lasers and cascaded Raman lasing [23][24][25][26][27]. In addition, nearly octave wavelength-tunable RFLs covering a 1-1.9 µm region have been realized by pump wavelength tuning and cascaded Raman shifting, whereas the S-, C-and L-band lasing requires a sixth-to eighthorder cascaded Raman process which requires a high threshold and for which it is difficult to control the lasing bandwidth due to the use of a broadband reflector [23][24][25][26][27][28][29]. On the other hand, the glass hosts (tellurite and bismuth oxide-based glasses) with high refractive indexes have been considered for expanding the gain bandwidth and the tunable range of fiber lasers.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the important members of the fiber laser family, the multi-wavelength fiber laser (MWFL) plays an irreplaceable role in wavelength-division multiplexed (WDM) communication systems, fiber sensing, optical signal processing, spectral analysis, high-resolution spectroscopy and photonic microwave technology [31][32][33][34]. Zhang et al achieved multiwavelength generation at 1.3 µm waveband in random fiber laser through four orders cascaded stimulated Raman scattering for the first time [35]. Tang et al demonstrated a MWFL based on dual-Sagnac comb filter with LP 11 modes output [36].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, RFLs have rapidly developed into a vital research interest in fiber lasers due to their clear advantages, including compactness, directionality, high efficiency, and low cost. Various RFL schemes have been proposed with different mechanisms, including nonlinear effects and rareearth-doped active fibers [6][7][8] , and wavelength adjustment and high-power random lasers are developing rapidly [9][10][11] . Due to their outstanding features, RFLs have broad application potential in the fields of high-quality imaging [12] , telecommunications [13] , sensors [14] , and nonlinear optics [15] .…”
Section: Introductionmentioning
confidence: 99%